Effect of Zn–Cd interdiffusion on the band structure and spontaneous emission of ZnO/Zn1−xCdxO/ZnO quantum wells. (September 2015) - Shtepliuk, I.; Khranovskyy, V.; Yakimova, R.
Highlights: We calculated the band structure for interdiffused ZnCdO/ZnO QWs. We have studied Zn–Cd interdiffusion effect on spontaneous emission spectra. We proposed optimized diffusion conditions providing high emission rate. Abstract: Needs in more-efficient visible light sources based on quantum wells (QWs) requires the diversification of traditional optoelectronics' materials as well as development of the cost-effective approaches for reliable quantum confinement engineering. Interdiffusion approach has a great potential to become a simple method for controlling the optical properties of QWs and diminishing the quantum confined Stark effect (QCSE). In this work we theoretically study the effect of Zn–Cd interdiffusion in ZnCdO/ZnO QWs on their band structure, optical matrix elements and spontaneous emission properties. The QW intermixing leads to improving both the transverse electric (TE) and transverse magnetic (TM) optical matrix elements due to enhancement of the overlap integral between electron and hole wave functions and modification of the confinement potential from triangle-shaped to parabolic-like. The optimized diffusion length 4 Å provided by the annealing at 700 K during 60 s was determined for 2 nm-thick Zn0.85 Cd0.15 O QW, which offers higher spontaneous emission rate in comparison to conventional QW. The reasonable interpretation of the interdiffusion effect on the optical properties of QWs is proposed in terms of low diffusion length and high diffusion length regimes. Thus, suitable combination of annealing duration and annealing temperature with the geometrical/compositional parameters of QWs can be the efficient way for improving the optical performance of ZnO-based QWs.